Pemberdayaan UMKM Rengginang Desa Dolok Kahean melalui Transformasi Digital - Muhammad Fawaz Elfikri; Salman Nasution (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a very important and strategic role in supporting the overall economic structure, with a contribution of 61.97% to the country's Gross Domestic Product (GDP). However, MSMEs, especially in rural areas, still face fundamental challenges, such as a lack of understanding and implementation of modern marketing and digital technologies. This service focuses on strategic efforts to empower Rengginang Ibu Saliem MSMEs in Dolok Kahean Village through a digital transformation program. The method used is descriptive qualitative Action Research, designed for direct program implementation and evaluation. The results of the pre-intervention showed that there was a severe digital gap in Rengginang products, although they had a tested taste, but still relied on traditional marketing models. Strategic intervention is carried out through two main pillars, namely, branding optimization by creating the trademark "Rengginang Huta" and a professional logo. Then the implementation of digital marketing through the construction of a virtual storefront on @rengginanghuta_ibusaliem's Instagram account. This program has succeeded in transforming these MSMEs into entities that are ready to compete in the digital ecosystem, in line with the statement that digitalization is the main imperative for MSMEs to survive. However, the evaluation stage identifies the issue of sustainability and digital independence as the next challenge. Long-term success requires more intensive post-program mentoring, focusing on digital operational management, to ensure independence and achieve real impact on improvement in Dolok Kahean Village.